Spatiotemporal patterns of egg predation in forest islands: an experimental approach - Tellería, J L; Santos, T (Biological Conservation, 1992)
Thirty holm oak Quercus rotundifolia forests, ranging from 0·1 to 350 ha, were studied in central Spain to analyse the spatial and temporal patterns of predation in relation to size of forest patches. During two springs (1988 and 1989), quail Coturnix coturnix eggs were placed in these forests to evaluate predation rates. Two trials (April and June) during each year were performed to study the intraseasonal and interyear constancy of predation. Results showed that predation rate tends to increase with forest fragmentation, although forest size was poorly related to predation rate. Predation rates seemed to be constant within spring seasons and between years. These results suggest that predators concentrate their search activities in some selected forests, thus accentuating their effect on prey species.
Keywords: Forest patches; forest size; fragmentation (voyant); predation rates